A Saffron-based Polyherbal Formulation DuK Prevents Hepatocellular Carcinoma in Male Wistar Rats - Gupta, Meenakshi; Nimesh, Hemlata; Bilgrami, Anwar L.; Sarwat, Maryam (Current Cancer Drug Targets, 2025)
BackgroundDuk is a well-established traditional drug that has been used since time immemorial by Indian practitioners to cure various human ailments.ObjectiveThe purpose of this study was to explore the anti-cancer activity and the possible mechanism of Duk against diethylnitrosamine (DEN)-initiated hepatocarcinogenesis.MethodsWe administered Duk at 3 doses, viz., 75, 150, and 300 mg/kg/day, 2 weeks before the DEN and continued it for 16 weeks. After 1 week of DEN recovery, 2-aminoacetylflourine (2-AAF) was administered to promote hepatocarcinogenesis.ResultsWe found that Duk significantly reduced the DEN and 2-AAF induced phenotypical changes in rats and restored the levels of liver function markers. Furthermore, Duk counteracted the oxidative stress induced by carcinogens as observed by restoration in the levels of superoxide dismutase (SOD) and catalase (CAT). Duk significantly diminished the levels of malondialdehyde (MDA) in a dose dependent manner and restored the liver microarchitecture as assessed by histopathological studies. The results of immunohistochemical staining showed that Duk inhibited the DEN-induced decrease in the number of cells positive for Bid and Caspase-9. It also reduces the number of cells positive for Cyclin D.ConclusionDuk significantly protects rat liver from hepatocarcinogenesis by regulating oxidative damage and restoring liver function markers. The chemopreventive effect of Duk might be through the induction of apoptosis.
Keywords: saffron